Immobilization of Yarrowia lipolytica for aroma production from castor oil - Braga, Adelaide (2013)
The main aim of this study was to compare different materials for Y. lipolytica immobilization that could be used in the production of γ-decalactone (a peach-like aroma) in order to prevent the toxic effect both of the substrate and the aroma upon the cells. Therefore, cells adsorption onto pieces of methyl polymethacrylate and of DupUM® was studied and further used in the biotransformation of castor oil into γ-decalactone. The highest aroma concentration was obtained with immobilized cells in DupUM®, where reconsumption of the aroma by the cells was prevented, contrarily to what happens with free cells. This is a very promising result for γ-decalactone production, with potential to be used at an industrial level since the use of immobilized cells system will facilitate the conversion of a batch process into a continuous mode keeping high cell density and allowing easier recovery of metabolic products.